(untitled) (Journal of Global Arts Studies, 2025)
Background: With the rapid advancement of digital technology revolution, emerging technologies are reshaping cultural inheritance paradigms. Henan Province possesses over 2,000 revolutionary sites but faces critical digital transformation challenges. Objective: This study aims to systematically assess the digital development level of red cultural resources in Henan Province and propose strategic pathways for digital technology empowerment. Methods: This study employs a mixed-methods approach based on the Delphi method and Analytic Hierarchy Process (AHP), conducting field research on 126 red cultural venues across 18 cities in Henan Province, combined with questionnaire surveys (n=1,089) and in-depth interviews (n=36). Results: Henan’s red culture digitalization development composite index is 2.68 (out of 5), indicating below-average performance. Digital communication scores highest (2.81), while industrial integration scores lowest (2.34). Significant regional disparities exist, with central cities (3.12) outperforming revolutionary areas (2.73) and general areas (2.31). Conclusion: Implementing hierarchical digital protection strategies, constructing immersive experience platforms, establishing omni-media communication networks, and developing digital creative industries can significantly enhance red cultural inheritance effectiveness.